2018
DOI: 10.1098/rspb.2018.1536
|View full text |Cite
|
Sign up to set email alerts
|

Bonobos voluntarily hand food to others but not toys or tools

Abstract: A key feature of human prosociality is , the most active form of sharing in which donors voluntarily hand over resources Direct transfers buffer hunter-gatherers against foraging shortfalls. The emergence and elaboration of this behaviour thus likely played a key role in human evolution by promoting cooperative interdependence and ensuring that humans' growing energetic needs (e.g. for increasing brain size) were more reliably met. According to the , among great apes only humans exhibit sufficiently strong pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 65 publications
(138 reference statements)
1
33
0
Order By: Relevance
“…Unlike chimpanzees, bonobos do not use tools for extractive foraging in the wild, and tool sharing may not support cultural transmission of tool use in bonobos. It is also possible that bonobos may value toys or tools differently than do chimpanzees (59).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike chimpanzees, bonobos do not use tools for extractive foraging in the wild, and tool sharing may not support cultural transmission of tool use in bonobos. It is also possible that bonobos may value toys or tools differently than do chimpanzees (59).…”
Section: Discussionmentioning
confidence: 99%
“…By , Call and Tomasello concluded that things had changed: several tasks provided converging evidence that apes were sensitive to the goals and intentions that underlie others' actions. For example, they were more patient with an individual who intended to feed them but was unable to do so than with one who was unwilling to share food, they discriminated and responded appropriately to intentional versus accidental actions, they helped others achieve their goals, and they completed others' failed actions (Buttelmann, Carpenter, Call, & Tomasello, ; Buttelmann, Schütte, Carpenter, Call, & Tomasello, ; Call, Hare, Carpenter, & Tomasello, ; Call & Tomasello, ; Krupenye, Tan, & Hare, ; Myowa‐Yamakoshi & Matsuzawa, ; Tomasello & Carpenter, ; Warneken, Hare, Melis, Hanus, & Tomasello, ; Warneken & Tomasello, ; Yamamoto, Humle, & Tanaka, ). There was also a variety of evidence suggesting that apes were aware of what others could see, and perhaps hear, and what others knew on the basis of seeing.…”
Section: Introductionmentioning
confidence: 99%
“…Only by retrieving and consuming their own food and transferring a tool to their partner could both benefit. This is the most salient difference to the study by Krupenye et al [67] and future studies could make an effort to combine the two designs in order to clarify possible explanations.…”
Section: Discussionmentioning
confidence: 87%